The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/0269216312463259
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of decision-making in requests for euthanasia: A qualitative research among patients, relatives and treating physicians in the Netherlands

Abstract: A patient's request for euthanasia entails a complex process that demands emotional work by all participants. It is characterised by an intensive period of sharing information, relationship building and negotiation in order to reach agreement. We hypothesise that making decisions about euthanasia demands a proactive approach towards participants' preferences and values regarding end of life, towards the needs of relatives, towards the burden placed on physicians and a careful attention to shared decision-makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
159
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(169 citation statements)
references
References 32 publications
1
159
0
Order By: Relevance
“…No physician, nurse or pharmacist shall be held criminally or civilly liable for assisting a person in the free exercise of this right. 3 A fundamental belief underlying the right to die (RTD) is that one's body and one's life are one's own to dispose of as one sees fit. Opponents of the RTD point out that legalizing the RTD may lead to irrational suicides.…”
Section: Letter Re: High Hypothetical Interest In Physician-assistedmentioning
confidence: 99%
See 2 more Smart Citations
“…No physician, nurse or pharmacist shall be held criminally or civilly liable for assisting a person in the free exercise of this right. 3 A fundamental belief underlying the right to die (RTD) is that one's body and one's life are one's own to dispose of as one sees fit. Opponents of the RTD point out that legalizing the RTD may lead to irrational suicides.…”
Section: Letter Re: High Hypothetical Interest In Physician-assistedmentioning
confidence: 99%
“…The concerns of Dr. Masdeu regarding the possible erosion of the physician-patient relationship and possible abuse are delineated elsewhere. 3,4 However, legal opinions, such as those of the Supreme Court of Canada, suggest a prohibition against PAD violates the rights of individuals with "grievous and irremediable medical conditions," 5 and that it is possible to enact structured procedures to address concerns related to abuse. 6 Whether the individual physician supports or opposes PAD, it is clear that people with multiple sclerosis are thinking about this issue and want to talk about it.…”
Section: Letter Re: High Hypothetical Interest In Physician-assistedmentioning
confidence: 99%
See 1 more Smart Citation
“…The public show greater support for euthanasia for advanced dementia than health professionals (Kouwenhoven et al 2012). Another Dutch qualitative study that elicited patient, family and physician views found that a patient's request for euthanasia entailed a complex process that demanded emotional work by all participants (Dees et al 2012). It was characterized by an intensive period of sharing information, relationship building and negotiation in order to reach agreement.…”
Section: Nursing Responses To Euthanasiamentioning
confidence: 99%
“…A request for euthanasia or PAS, documented in a written advance directive is not a right of a patient but a request, without binding legal consequences [4]. Physicians generally do not initiate a conversation about end-of-life wishes and have difficulty handling an advance directive even though situations for which the advance directive was intended were recognized [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%